ZIF-8 calcination derived Cu2O–ZnO* material for enhanced visible-light photocatalytic performance. (28th January 2021) - Yin, Yilin; Liu, Jingchao; Wu, Zengnan; Zhang, Ting; Li, Zenghe
Abstract : The mechanism of TC degradation over Cu2 O–ZnO* rich in oxygen vacancies. Abstract : As one of the most essential semiconductors, ZnO has been widely used for solar cells, photocatalysis, environmental remediation, etc. Doping and morphology control of ZnO can significantly improve the efficiency of its photocatalytic performance. Tetracycline hydrochloride (TC) is widely used in medical and veterinary fields. Its excess use harms the environment and human health. Herein, we have successfully prepared Cu2 O-doped ZnO with a porous structure by calcination using ZIF-8 as the precursor. After exposure to visible light ( λ >420 nm) for 75 min, these photocatalysts exhibited a reasonable TC degradation rate (∼83.6%). Compared with ZnO, the Cu2 O-doped ZnO introduces a p–n heterojunction and increases oxygen vacancies, which reduces the band gap and electron–hole recombination. Therefore, the photocatalytic efficiency for TC and PEC performance have been improved.